A damaging block-based model for the analysis of the cyclic behaviour of full-scale masonry structures. (15th March 2019) - D'Altri, Antonio Maria; Messali, Francesco; Rots, Jan; Castellazzi, Giovanni; de Miranda, Stefano
Highlights: A damaging block-based model is proposed for the cyclic analysis of masonry structures. Tests on small-scale specimens are used to calibrate the mechanical properties of the model. In-plane, out-of-plane and full-scale cyclic tests on masonry structures are simulated. A good agreement between the numerical results and the experimental outcomes is observed. Abstract: In this paper, a damaging block-based model is proposed for the numerical analysis of the cyclic behaviour of full-scale masonry structures. Solid 3D finite elements governed by a plastic-damage constitutive law in tension and compression are used to model the blocks, while a cohesive-frictional contact-based formulation is developed to simulate their cyclic interaction. The use of tests on small-scale specimens to calibrate the mechanical properties of the numerical model is presented and discussed. The tests belong to a comprehensive experimental campaign performed on calcium silicate brick masonry. The calibrated models are used to simulate in-plane and out-of-plane cyclic tests on masonry walls made of the same material, as well as a quasi-static cyclic pushover test on a full-scale terraced masonry house. The efficiency, the potentialities and the accuracy of the model here proposed are shown and discussed. The capability of explicitly representing structural details (e.g. running bonds) and any in-plane and through-thickness texture of masonry, which appears essential to study the response of masonry structures, is guaranteed by the block-based modelling approach. A good agreement between the numerical results and the experimental outcomes is observed. This allows to validate the model in the cyclic response as well as the strategy proposed for its mechanical characterization.